Estimation of anaerobic threshold by cardiac repolarization instability: a prospective validation study - Dominik Schüttler; Simone Krammer; Lukas von Stülpnagel; Lauren Sams; Axel Bauer; Wolfgang Hamm; Stefan Brunner (BMC, 2021)
Abstract Background Assessing lactate (LT) or anaerobic thresholds (AT) in athletes is an important tool to control training intensities and to estimate individual performance levels. Previously we demonstrated that ECG-based assessment of cardiac repolarization instability during exercise testing allows non-invasive estimation of AT in recreational athletes. Here, we validate this method in professional and amateur team sports athletes. Methods We included 65 team sports athletes (32 professionals and 33 amateur athletes; 51 men, 14 women, mean age 22.3 ± 5.2 years) undergoing a standardized incremental cycle exercise test. During exercise testing a high-resolution ECG (1000 Hz) was recorded in Frank-leads configuration and beat-to-beat vector changes of cardiac repolarization (dT°) were assessed by previously established technologies. Repolarization-based AT (ATdT°) was estimated by its typical dT°-signal pattern. Additionally, LT was detected in accordance to methods established by Mader (LTMader) and Dickhuth (LTDickhuth). Results All athletes performed exercise testing until exhaustion with a mean maximum workload of 262.3 ± 60.8 W (241.8 ± 64.4 W for amateur athletes and 283.4 ± 49.5 W for professional athletes). Athletes showed ATdT° at 187.6 ± 44.4 W, LTDickhuth at 181.1 ± 45.6 W and LTMader at 184.3 ± 52.4 W. ATdT° correlated highly significantly with LTDickhuth (r = 0.96, p < 0.001) and LTMader (r = 0.98, p < 0.001) in the entire cohort of athletes as well as in the subgroups of professional and amateur athletes (p < 0.001 for all). Conclusions ATdT°, defined by the maximal discordance between dT° and heart rate, can be assessed reliably and non-invasively via the use of a high-resolution ECG in professional and amateur athletes.